MEMBANGUN HUBUNGAN YANG BAIK ANTARA GURU DAN SISWA - Ani Kurniawati; Basuki Basuki (Kurikula : Jurnal Pendidikan, 2023)
In the learning process, teachers and students have a very important role, because the success or failure of an educational goal is determined by the role of both. If teachers and students know and perform their roles well, of course, there is no difficulty in achieving educational goals. The writing of this scientific paper aims to find out how to build a good relationship between teachers and students. This research uses the literature method by collecting several books, journals, articles and several related ones to be used as reference material. As for data analysis, it uses content analysis. This research produced the following findings: 1) the importance of building a good relationship between teachers and students so that the learning process can run well, 2) some efforts that must be made by teachers to realize such good relationships by understanding students' abilities, respecting students' opinions and suggestions, building good cooperation between students and also being fair in treating students